Osmium-free direct syn-dihydroxylation of alkenes. - Bataille, C; Donohoe, T (2011)
Numerous synthetic protocols for producing syn-diols from the corresponding alkenes have been developed and published over recent years. It is the intent of the following tutorial review to present a concise summary of the main methods used to prepare syn-diol fragments directly from alkene precursors, and that do not make use of osmium oxo complexes as catalysts.